2020
DOI: 10.1038/s41598-020-63254-7
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to cellular stress in PS1 mutant N2a cells is associated with mitochondrial defects and altered calcium homeostasis

Abstract: Presenilin 1 (PS1) mutations are the most common cause of familial Alzheimer's disease (FAD). PS1 also plays a role in cellular processes such as calcium homeostasis and autophagy. We hypothesized that mutant presenilins increase cellular vulnerability to stress. We stably expressed human PS1, mutant PS1E280A and mutant PS1Δ9 in mouse neuroblastoma N2a cells. We examined early signs of stress in different conditions: endoplasmic reticulum (ER) stress, calcium overload, oxidative stress, and Aβ 1-42 oligomers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Additionally, recent reports showed that mitochondria had neuron‐impairment effect 40 , 41 , 42 and mtDNA had an inflammatory‐promoting effect, 28 , 29 , 30 but the pathological mechanism was still oblivious. Our results showed when mtDNA interacted with cerebral tissue, neutrophil infiltration was activated and the neuron apoptosis process was initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent reports showed that mitochondria had neuron‐impairment effect 40 , 41 , 42 and mtDNA had an inflammatory‐promoting effect, 28 , 29 , 30 but the pathological mechanism was still oblivious. Our results showed when mtDNA interacted with cerebral tissue, neutrophil infiltration was activated and the neuron apoptosis process was initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of lipid catabolism and suppression of autophagy would be expected to produce small mitochondria, and an increased level of lipid in liposomes. Indeed, mutations in presenilin-1 produce small, dysfunctional mitochondria, and produce an accumulation of lipid ( Sarasija et al, 2018 ; Rojas-Charry et al, 2020 ; Han et al, 2021 ).…”
Section: Models For Studying Alzheimer’s Disease Cellular and Molecul...mentioning
confidence: 99%
“…19 PSEN1 mutations lead to mitochondrial permeability transition pore (mPTP) opening, thus making cells more sensitive to apoptotic stimuli. 19,20 Predicted by bioinformatics tools (TargetScan, starbase, and PicTar), we found that PSEN1 is a novel putative target of miR-141-3p. Therefore, we propose a hypothesis that miR-141-3p regulates palmitic acid (PA) induced myocardial lipotoxic injury in vitro through targeting of PSEN1.…”
mentioning
confidence: 91%